The catena aspect of the landscape diversity of the «Dnipro-Orilsky» natural reserve - Gritsan, Yurii; Грицан, Юрій Іванович; Kunakh, O.; Кухан, О. М.; Dubinina, J.; Дубініна, Ю. Ю.; Kotsun, V.; Коцун, В. І.; Tkalich, Yuriy; Ткаліч, Юрій Ігоревич (Дніпровський національний університет імені Олеся Гончара, 2019)
In the present investigation catena approaches to assess the landscape diversity of the “Dnipro-Orilsky” natural reserve was developed. Catena which lies in the reserve embraces flood and arena biogeocoenoses. The research was performed during the 2014– 2018. The two profiles were made at the “Dnipro-Orilsky” natural reserve within which main geomorphological landscape elements are presented. There are 29 sampling polygons within these p rofiles. The soil profile description, vegetation investigation, soil and soil animals quantitative assessment was carried out in each of them. In this publication we presented the results of sampling polygons 1–4, 25 and 26. The profile 1 best reflects the traditional view of catena: it goes from the highest places of the sand terrace (arena) to the lowest place (floodplain). But relief diversity is increased by the availability of small river Protich. It floodplain provides an alternative transit and accumulation gradient. It should be noted that the main part of the main slope profile does not fully meet the transit regime, as compiled by sandy soils, which are char- acterized by high filtration capacity. Therefore, the slope profile position is largely corresponded to eluvial regimes. The accumulative part of the profile which corresponds to the floodplain of Dnipro river is significantly influenced by impact of the flood factor than the accumulative part of the profile which corresponds to the floodplain of Protich river. The soils within floodplain of Protich river have more quantity of clay. Clay soils are characterized by capillary properties, as soil salinization is common in the floodplain of Protich river. Alternative profile 2 includes Orlov valley. This element of the landscape is accumulative, but not affected by flood factor. In the biogeocenotic context catena sampling points were considered as being composed of pedocatena, phytocatena and zoocatena. The biogeocenotic approach is the chain that connects the landscape structure, the diversity of soil cover, and diversities of the plant and animal communities. The functional, spatial and temporal properties of ecosystems in landscape context can be expressed by catena. The biogeocoenosis concept is a basis for integration of the pedocatena, phytocatena and zoocatena. Catena approach is the framework for a monitoring system landscape diversity both at the level of individual component biogeocoenosis (edaphotop, phytocenosis, and zoocenosis) and biogeocoenosis level in terms of its horizontal and vertical structure and at the landscape level as a whole intercon- nected system. The traditional idea of catena as a set of eluvial, transit and accumulative positions in a complex and diverse landscape is not able to cover the most important environmental gradients modes. The complexity of the landscape is due to relief diversity and the effects of anthropogenic transformation biogeocenotic cover. Catena therefore can be seen as a multilevel hierarchical system of the biogeocenotic polygons needed to consider the diversity of physiographic conditions and anthropogenic gradients. У дослідженні був розроблений катений підхід для оцінки ландшафтного різноманіття природного заповіднику «Дніпровсько-Орільський». Катена, яка знаходиться у заповіднику, охоплює заплавні та арені біогеоценози. Дослідження проводилося протягом 2014–2018 рр. У межах природного заповіднику «Дніпровсько-Орільський» закладені два профілі, у межах яких представлені основні геоморфологічні елементи ландшафту. Уздовж профілів розміщені 29 експериментальних полігонів. Описи грунтового профілю, вивчення рослинності, ґрунтів і кількісна оцінка ґрунтових тварин були проведені в кожному з цих полігонів. У цій публікації ми представили результати по полігонам 1–4, 25 і 26. Профіль 1 найкраще відображає традиційне уявлення про катену: він йде з найвищих місць на боровій терасі (арена) до найнижчого місця (заплава р. Дніпро). Але різно- манітність рельєфу збільшується за рахунок наявності малої річки Протіч. Її заплава забезпечує альтернативний транзитний і акумулятивний градієнти. Основна частина головного профілю схилу не у повній мірі відповідає транзитного режиму, так як він складений з піщаних ґрунтів, які характеризуються високою фільтруючою здатністю. Таким чином, положення про- філю схилу в значній мірі відповідає елювіальний режимам. Акумулятивна частина профілю, яка відповідає заплаві річки Дніпра, в значній мірі залежить від впливу фактора повені, ніж акумулятивна частина профілю, яка відповідає заплаві річки Протіч. Ґрунти у межах заплави річки Протіч мають більший вміст глини. Глинисті ґрунти характеризуються капілярними властивостями, тому і засолення грунту значно більш поширене у заплаві річки Протіч. Альтернативний профіль 2 включає в себе Орлову балку. Цей елемент ландшафту є накопичувальним, але не зазанє впливу фактору повені. У біогеоценотичному контексті катену розглядають як сукупність точок відбору проб, які складаються з педокатени, фітокатени і зоокатени. Біогеоценотичний підхід є ланцюгом, що з’єднує структуру ландшафту, різноманітність ґрунтового покриву і різноманітність рослинних і тваринних угруповань. Функціональні, просторові і часові властивості екосистем в ландшафтному контексті можуть бути виражені за допомогою катени. Біогеоценотична концепція є основою для інтеграції педокатени, фітокатени і зоокатени. Катений підхід є основою для системи моніторингу ландшафтного різноманіття як на рівні окремих компонентів біогеоценозу (едафотоп, фітоценоз та зооценоз), на біогеоценотичному рівні в аспекті його горизонтальної та вертикальної структури та і на ландшафтному рівні у якості цілістної системи взаємопов’язаних частин. Традиційне уявлення про катену як набір елювіальних, транзитних та акумулятивних позицій не може повною мірою відобразити найбільш важливі градієнти екологічних режимів. Складність ландшафту виникає внаслідок різноманіття рельєфу та ефектів антропогенної трансформації біогеоценотичного покриву. Тому катена може розглядатися як багаторівнева ієрархічна система біогеоценотичних полігонів, яка необхідна для характеристики різноманіття фізико-географічних умови і антропогенних градієнтів.
Катений аспект ландшафтного різноманіття природного заповіднику «Дніпровсько-Орільський».
Keywords: catena; катена; landscape; ландшафт; soil; ґрунт; natural reserve; природний заповідник; diversity; різноманіття